A Review on Innovative Nanocellulose Solutions for Wastewater Treatment and Reusability of Nanocellulose (London Journal of Research In Science: Natural and Formal, 2025)
About 14,000 individuals lose their lives every day as a result of exposure to certain toxins in the environment. Reducing these pollutants to acceptable levels using existing methods including adsorption, biodegradation, oxidation, precipitation, reverse osmosis, and photocatalysis is costly, energy-intensive, and unsustainable. A novel method of cleaning up these chemical pollutants combines biosorption with nanotechnology. Nanocellulose (NC) has been widely utilized to cleanse water. According to reports, nanocellulose may be utilized to eliminate various contaminants from water systems, such as dyes, heavy metals, medications, pesticides, medicines, and microbiological cells. There is a lot of interest in wastewater management globally in developing practical treatment methods to guarantee the supply of clean water. The abundance of -OH groups that allow nanocellulose to bond with heavy metals, dyes, and other pollutants and high aspect ratio are its specializations for this specific application. This review summarizes the application of nanocellulose in wastewater treatment, namely as heavy metal, oil, salts, and dye adsorbents and as membranes for filtering other pollutants, such as microorganisms. The effectiveness of nanocellulose over conventional methods towards wastewater treatment is also reviewed. Applicability of cellulosic nanomaterials in wastewater treatment as well as aspects of nanocellulose as an adsorbent for diverse water contaminants are highlighted in this review. The broad application of materials based on nanocellulose as adsorbents and catalysts is made possible by the commercial processing of cellulose. The membrane technologies' longevity and efficacy in separating materials have been demonstrated. Recent advancements in the creation of innovative membranes or adsorbents promote the use of cleaner technologies based on NC for treatment of wastewater. Future research prospects of nanocellulose composites for wastewater treatment are also discussed, along with the difficulties and possibilities of nanocellulose-based composites in these fields.
Keywords: heavy metals; Desalination; Modification; Membrane; Nanocellulose; Reusability; Water Treatment